The Making of Science Smart i-THINK: Science Expert Teachers’ Evaluation - Azid, Nurulwahida; Shaik-Abdullah, Sarimah; Hashim Mohamed, Zuhailah (International Journal of Engineering and Technology, 2018)
Science Smart i-Think is an interactive pedagogical tool that was created to facilitate the learning of science among 30 year five rural primary pupils, specifically on the topic Earth, Moon and Sun.  The application was intended to enhance higher order thinking skills (HOTS) based on ADDIE model, advanced organizer and mastery learning.   It incorporates the following eight thinking maps:  circle map, bubble map, double bubble map, tree map, brace map, flow map, multi-flow map and bridge map. Reviewers provided favourable responses on various features in the application (e.g. animation, user-friendliness) that make learning interesting and effective.